Graduate Students’ Perceptions of Online Learning: Implications for Distance Education Programs - Natividad-Franco, Virginia; Espino, Joseph D. (Future Science / FSH-PH Publications, 2025)
Online learning greatly supports the offering of distance education by providing innovative platforms. This study examined graduate students’ perceptions of online learning as a basis for offering distance education. It utilized the concurrent mixed method. The respondents of the study are the graduate school students at La Consolacion University, Philippines, enrolled during the 2nd trimester of the school year 2022–2023. The quantitative results of the study have a weighted mean of 3.71, which showed strong agreement on online learning activities, strategies, media, and support instruments. Qualitative analysis revealed three perceived advantages: innovative engagement, convenience, and flexible scheduling. It was then concluded that the study highlighted that online learning could be an effective and innovative practice for graduate school students. Constant efforts must be made to improve the online learning environment in response to student feedback and to alter educational paradigms to preserve the high standard of online education. The findings imply that distance education programs should continue enhancing online learning activities, strategies, and tools to sustain positive student perceptions. With convenience, flexibility, and innovative engagement as key advantages, institutions must invest in digital resources, faculty training, and support systems while ensuring continuous feedback to maintain quality and relevance in graduate education.